Optimal sizing of a wind-photovoltaic-battery hybrid renewable energy system considering socio-demographic factors - Tito, SR; Lie, T; Anderson, TN (Elsevier, 2016)
The sizing of a stand-alone wind-photovoltaic-battery hybrid renewable energy system (HRES) is greatly influenced by socio-demographic factors however, few studies have examined how socio-demographic factors, as borne out by different electrical usage patterns, influence the size of HRESs. This paper investigates how these factors influence the optimal sizing of a stand-alone HRES using a hybrid optimization method to match the available renewable energy with the demand. In this regard, different energy usage patterns resulting from users socio-demographic profile have been investigated and used for the optimal sizing of a HRES. The results show that the electricity usage profile of a site has a significant impact on the sizing and design of the system. Further, the results illustrate that one can design a system that meets the demand profiles resulting from socio-demographic factors with a minimum unmet load; however, by optimizing systems to the users socio-demographic profile, significant cost savings can be made.
Keywords: Hybrid renewable energy system; Stand-alone; Sizing; Socio-demographic factors; Load profile